Relação entre esperança, funcionamento cognitivo e sintomas depressivos em idosos - Pedone, Márcia Rejane Estima (2021)
Elderly population has been increasing, and the projection for the future is that this number will grow. However, it is necessary that, as people get older, they have quality of life, and themes, such as hope, cognitive functioning and depressive symptoms, should be explored more academically, as they are very relevant. So, the general objective of this research was to verify the relationship between hope, cognitive functioning and depressive symptoms in the elderly; and the specific ones were to characterize the elderly in relation to their levels of hope, cognitive functioning and depressed symptoms; find out if there was a relationship between sociodemographic characteristics and levels of hope, cognitive functioning and depressed symptoms; verify if the levels of hope have influenced the cognitive functioning of the elderly and the depressive symptoms; and find out what factors can contribute to the better cognitive performance of the elderly. It is an observational, cross-sectional study with a descriptive analytical approach. The instruments used were Mini-Mental State Examination (MEEM), for sample selection, the Consortium to Establish a Registry for Alzheimer's Disease (CERAD), the Dispositional Hope Scale and the Geriatric Depression Scale (GDS-15). The sample was composed by 101 elderly people, and 20 were excluded, since they had scores below 28 points in the MEEM, so 81 were analyzed. They were 60 years old or older, had no cognitive deficits and participated in different elderly community centers in Porto Alegre, in the Metropolitan Region. The correlation analyzes (Spearman) between the Dispositional Hope Scale were compared with the CERAD and GDS instruments. In the List of Words, we verified that it was significantly related to the Dispositional Hope Scale, pointing to higher average Hope scores in the group of respondents, with an expected classification for the total Hope (p = 0.001) and the paths dimension (p = 0.011). These factors can lead these individuals to a better cognitive performance in Boston naming tasks, Verbal Fluency, Semantic Verbal Fluency and Phonological Fluency and Language, Executive Function, Long Term Memory. Hope is a positive adaptation, a protective factor of the psyche and of transforming negative behaviors, thoughts and feelings into new possibilities, enabling the elderly to cope with the cumulative stressful circumstances and events of life. High levels of hope and without the presence of depressive symptoms have contributed to these individuals to have a better cognitive performance in Boston Naming tasks, Verbal Fluency and Semantic Fluency, Phonological Fluency and Language, Executive Function and Long-Term Memory.